2015
DOI: 10.1111/clr.12566
|View full text |Cite
|
Sign up to set email alerts
|

Host‐derived biomarkers at teeth and implants in partially edentulous patients. A 10‐year retrospective study

Abstract: Increased levels of MMP-8 and IL-1β in PISF or GCF may be associated with inflammation around teeth and implants while lower levels of MMP-1/TIMP-1 may be an indicator of disease progression around implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 51 publications
11
59
0
2
Order By: Relevance
“…18,19 Moreover, research indicates that nicotine in tobacco upregulates the secretion of proinflammatory cytokines (such as IL-1b and MMP-9), which play a key role in alveolar bone deterioration around natural teeth. 20,21 Increased expression of these proinflammatory cytokines have also been detected in the PISF of patients with peri-implantitis. 22,23 Furthermore, findings from a recent meta-analysis showed that tobacco smoking impairs new bone formation around dental implants and jeopardizes bone-to-implant contact.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Moreover, research indicates that nicotine in tobacco upregulates the secretion of proinflammatory cytokines (such as IL-1b and MMP-9), which play a key role in alveolar bone deterioration around natural teeth. 20,21 Increased expression of these proinflammatory cytokines have also been detected in the PISF of patients with peri-implantitis. 22,23 Furthermore, findings from a recent meta-analysis showed that tobacco smoking impairs new bone formation around dental implants and jeopardizes bone-to-implant contact.…”
Section: Discussionmentioning
confidence: 99%
“…One of them reported no significant change after de novo plaque accumulation [25]. Thirteen studies showed higher levels of IL-1β in PICF than healthy implant sites [7,21,22,30,35,36,41-47]. Of the 10 studies assessed TNF-α, 3 of them showed no relationship with this cytokine with peri-implant inflammation [7,25,43], while other 7 studies showed significant relationship with this cytokine [23,24,36,41,46-48].…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, several studies have examined different biologic mediators such as interleukin 1 beta, prostoglandin, matrix metalloproteinases, and proteolytic enzymes in peri‐implant diseases . However, there are very limited number of studies evaluating PISF osteocalcin, osteopontin, and osteonectin levels in different peri‐implant diseases.…”
Section: Discussionmentioning
confidence: 99%